2012
DOI: 10.5897/ajb11.651
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of anti-bacterial properties of ethanol extract of Ficus exasperata leaf

Abstract: This study evaluated the antibacterial effect of ethanolic extract of Ficus exasperate leaf. Clinical isolates of Escherichia coli, Pseudomonas aeruginosa, Staphyllococcus aureus and Klebsiella pneumoniae were incubated in agar plates after serial dilutions of the extract were added in wells made in the agar and incubated for 24 h at 37°C. Thereafter, zones of inhibition (in mm) around the wells were measured. The same organisms were tested for sensitivity against standard antibiotics using disk diffusion. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
(7 reference statements)
0
3
0
Order By: Relevance
“…Odunbaku et al had earlier found the MIC of this extract against E.coli to be 300mg/ml [7] . This high MIC (low activity) could be due to differences in geographical location, season of plant, age of the plant, and method of extraction, all of which affect the yield and the active constituents of medicinal plants [8], [9] .It could also be due to differences in laboratory procedures and reagents used [10], [11] .The MICs observed in this study were also lower than those of another medicinal plant, Ficusexasperatawhose MIC was 100mg/ml against K.pneumoniae and 25mg/ml against E.coli, S.aureus, and Ps.aeruginosa [4] . Minimum inhibitory concentrations (the lowest concentration of drug which inhibits growth) are used by diagnostic laboratories to determine in vitro activity or resistance to both old and new antimicrobial agents [12] .…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Odunbaku et al had earlier found the MIC of this extract against E.coli to be 300mg/ml [7] . This high MIC (low activity) could be due to differences in geographical location, season of plant, age of the plant, and method of extraction, all of which affect the yield and the active constituents of medicinal plants [8], [9] .It could also be due to differences in laboratory procedures and reagents used [10], [11] .The MICs observed in this study were also lower than those of another medicinal plant, Ficusexasperatawhose MIC was 100mg/ml against K.pneumoniae and 25mg/ml against E.coli, S.aureus, and Ps.aeruginosa [4] . Minimum inhibitory concentrations (the lowest concentration of drug which inhibits growth) are used by diagnostic laboratories to determine in vitro activity or resistance to both old and new antimicrobial agents [12] .…”
Section: Discussionmentioning
confidence: 59%
“…Screenings of medicinal plants for antimicrobial activities are important for finding potential new compounds for therapeutic use.Medicinal plants readily provide sources of such novel agents. Herbs known to have antibacterial properties includeAcacia arabica, Nymphaea lotus, Sphareranthushirtus, Emblicaofficinalis, Cinchoriumintybus, Cardusmarianum, and Ficusexasperata [3], [4] .However, most of the antimicrobial studies on this plant were done using the ethanol extract. Even in traditional medical practice most of these plants are usually soaked in local gin to extract the active constituents.…”
Section: Introductionmentioning
confidence: 99%
“…The basic qualitative measures of the in vitro activity of antimicrobials are the minimum inhibitory concentrations {MIC} or minimum bacterial concentration {MBC} [35]. The minimum inhibitory concentration {MIC} is the least concentration of an antimicrobial that shows no growth of microbial isolates in broth or agar.…”
Section: Qualitative Phytochemical Constituent Of Newbouldia Laevis Lmentioning
confidence: 99%